Current state of knowledge on the use of cannabidiol (CBD) in various medical conditions - Zuzanna Lubczyńska; Jakub Przeradzki; Aleksandra Borycka; Maria Kotulska; Martyna Lichman; Barbara Jędrzejewska; Paulina Laskus; Zofia Potocka; Nikola Siekierko; Maja Żołnierek (Kazimierz Wielki University, 2023)
INTRODUCTION AND PURPOSE Cannabis sativa contains hundreds of compounds, referred to as cannabinoids. Two most prevalent are delta-9-tetrahydrocannabinol and cannabidiol (CBD). CBD is non-psychoactive substance that has recently gained attention in lay press and in medical research. Aim of this study is to review evidence-based data on safety, effectiveness and applicability of CBD in various medical conditions in order to provide healthcare professionals with information that may be useful in their practice. MATERIALS AND METHODS In April 2023, PubMed and Google Scholar databases were searched for studies that included phrases "CBD" or "cannabidiol", and related phrases. In the review, only studies that used well-established research methods were included. RESULTS CBD is an effective novel treatment option in Lennox-Gastaut syndrome, tuberous sclerosis complex and Dravet syndrome. Data supporting CBD's applicability in anxiety, Parkinson's Disease, schizophrenia, insomnia, pain, autoimmune diseases, osteoporosis and as an anti-aging agent is promising, but more research on bigger groups of patients is needed to establish its role in modern medicine. CONCLUSIONS The use of CBD is associated with risks of variable dosage, contamination and adulteration. At present, there is a need of more research to establish effective and safe doses of CBD. Clinicians need to monitor new data from ongoing CBD trials, but at present there is no hard evidence supporting effectiveness of CBD in various medical conditions, apart from epilepsy.